2019
DOI: 10.1007/s12028-019-00697-5
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy After Severe Acute Brain Injury: Trends and Variability in the USA

Abstract: Background/Objective: Severe acute brain injury (SABI) is responsible for 12 million deaths annually, prolonged disability in survivors, and substantial resource utilization. Little guidance exists regarding indication or optimal timing of tracheostomy after SABI. Our aims were to determine national trends in tracheostomy utilization among mechanically ventilated patients with SABI in the USA, as well as to examine factors associated with tracheostomy utilization following SABI. Methods:We conducted a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…Tracheostomy is a frequently performed procedure in the intensive care unit (ICU) [ 13 , 49 ], with 10–15% of patients in polyvalent ICUs [ 1 ] and 15–46.8% in neurocritical care patients [ 21 , 32 ]. In mechanically ventilated patients in the ICU – irrespective of the nature of the underlying disease – tracheostomy is used to prevent laryngeal and tracheal damage, to reduce the need for sedation, to shorten the duration of mechanical ventilation (MV), to increase patient comfort and to reduce the length of stay (LOS) in the ICU [ 13 , 26 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tracheostomy is a frequently performed procedure in the intensive care unit (ICU) [ 13 , 49 ], with 10–15% of patients in polyvalent ICUs [ 1 ] and 15–46.8% in neurocritical care patients [ 21 , 32 ]. In mechanically ventilated patients in the ICU – irrespective of the nature of the underlying disease – tracheostomy is used to prevent laryngeal and tracheal damage, to reduce the need for sedation, to shorten the duration of mechanical ventilation (MV), to increase patient comfort and to reduce the length of stay (LOS) in the ICU [ 13 , 26 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the indication for tracheostomy may be considered to be wider and easier compared with that of the past in patients with acute brain injury. A recent study reported an increase in tracheostomy utilization in the USA among patients with severe acute brain injury [25]. The increasing trend of tracheostomy has arisen from positive reasons such as easy weaning from the ventilator, facilitation of earlier discharge from intensive care, improved patient safety, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trend of tracheostomy has arisen from positive reasons such as easy weaning from the ventilator, facilitation of earlier discharge from intensive care, improved patient safety, etc. [25]. Also, tracheostomy and its timing have been hypothesized to be associated with clinical outcomes [26].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ARF associated with TBI has decreased over the last decade due to improvements in extra-and intrahospital management. However, it still remains one of the main causes of morbidity and mortality, and the incidence of residual respiratory failure at the end of acute hospitalization is approximately 32% [24,25].…”
Section: Traumatic Brain Injurymentioning
confidence: 99%